2006
DOI: 10.1143/ptp.116.169
|View full text |Cite
|
Sign up to set email alerts
|

Sizes of the Lightest Glueballs in SU(3) Lattice Gauge Theory

Abstract: Standard Monte Carlo simulations have been performed on improved lattices to determine the wave functions and the sizes of the scalar and tensor glueballs at four lattice spacings in the range a = 0.05 − 0.145 fm. Systematic errors introduced by the discretization and the finite volume are studied. Our results in the continuum limit show that the tensor glueball is approximately two times as large as the scalar glueball.PACS numbers:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 17 publications
0
32
1
Order By: Relevance
“…In addition, it is perhaps worth mentioning that some lattice studies [57] found indication that heavier glueball states tend to have better overlap with more extended (rather than more localized) operators. We do not think that these results are necessarily in contradiction with our findings, because, as we already remarked, the eigenvalue parameters that we fitted are not to be interpreted as strictly equivalent to the physical volume of each state: rather, they account for the effects of glueball interactions, and describe the effective volume of each state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is perhaps worth mentioning that some lattice studies [57] found indication that heavier glueball states tend to have better overlap with more extended (rather than more localized) operators. We do not think that these results are necessarily in contradiction with our findings, because, as we already remarked, the eigenvalue parameters that we fitted are not to be interpreted as strictly equivalent to the physical volume of each state: rather, they account for the effects of glueball interactions, and describe the effective volume of each state.…”
Section: Discussionmentioning
confidence: 99%
“…The lattice glueballs are compact objects, the scalar glueball has a radius of about 0.3 fm [148]. According to Forkel [149] direct instanton contributions dominate over those from perturbative fluctuations or from soft vacuum fields.…”
Section: Glueballsmentioning
confidence: 99%
“…The spectrum of stable bound states includes several glueballs with different quantum numbers J P C . Some of these glueballs have been studied in some detail in various contexts; see for example [13,14,15,16,17,18,19] and a recent review [20]. The masses of the v-glueballs are determined by the confinement scale Λ v or, equivalently, the string tension σ through the relationship m 0 ++ ≈ 7Λ v ≈ 3.7σ.…”
Section: Introductionmentioning
confidence: 99%
“…(A- 19) Therefore, there are five form factors in the J → J ′ = 2 case. The general rule to find all the form factors in the case J → J ′ case is now clear.…”
mentioning
confidence: 99%